BIOMONITORING OF SEVOFLURANE EXPOSURE IN ANESTHESIOLOGIST - Firly Ratsmita; Muhammad Ilyas (The Indonesian Journal of Public Health, 2021)
ABSTRACTSevoflurane is used by anesthetists for the induction and maintenance of general anesthesia. This causes the anesthetist to get daily exposures. This will be a potential hazard for exposed operating room personnel, especially anesthetists. The adverse health effects of sevoflurane as hepatotoxic, nephrotoxic and neurotoxic in the human body can be a risk for anaesthetists. Biological monitoring can be done by measuring the levels of sevoflurane and its metabolites or by looking at biomarkers for their effects on health effects. The aim of this study was to seek a literature review on the biomonitoring of sevoflurane exposure in anaesthetists. We searched the literature review using the PRISMA method in PubMed and Google scholar using the following keywords "occupational disease" "chronic effects" "anaesthetist" "sevoflurane exposure" "inorganic fluoride" "biomarkers" previously using the term MeSH and combined with Boolen "OR" and AND". We obtain 75 articles taken from the database, excluded 35 articles, and selected 5 articles. The results of the review articles showed that there were health effects, especially on liver and kidney function in chronic exposure. Biological monitoring can be undertaken by detecting sevoflurane and its metabolites in the urine during work and function of the liver and kidneys. The evidence for biological monitoring as surveillance in anaesthesiologists remain inconsistent due to limited studies. We recommend to measure sevoflurane in ambient air using a hierarchy of controls, such as elimination, replacement, engineering, administrative and personal protective equipment. We need to undertaken environmental and biological monitoring in order to acquire a safe and healthy work environment. Keywords: sevoflurane exposure, occupational health, anesthesiologist